Temporality, flexibility, durability:: A new attitude for architectural education? - CHARDONNET- DARMAILLACQ, Sabine (ARCC Conference Repository, 2019)
At the time of modernity, the perfect adequacy of the architectural object to its use was enough to meet its legitimacy. In the perspective of sustainable development, the architectural object becomes "environmental". Building product cannot be considered anymore, as regards form, as finite and determined or established. It has to integrate open thought in terms of resources management as well as usage or social practice mutations. Rapid mutations in various domains of urban and domestic life lead us into considering temporality related questions. Immutability and perpetuity of built space are firmly fixed notions strongly related to a representation of building as an object of transmission of property or political power (public buildings seen as monuments). A technical consequence of this conception of buildings being the durability, long life span and rigidity of pieces of work that compose them. Yet by the time, these notions are being discussed and rapid evolution of our societies lead to a demand for frequent changes of functions, destinations and picture of built space, considered internally and externally.